Pengaruh Kualitas Sistem Informasi Akuntansi, Norma Subyektif dan Kemudahan Penggunaan pada Kinerja Individu - Saraswati, Ni Luh Made Galih Putri; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2018)
Information is one of the business resources. Information system quality and company success are influenced by individual performance. The performance of individuals with accounting information systems that are supported by subjective norms and ease of use of the system. This study aims to examine and provide empirical evidence about the factors that can lead to the success of the accounting information system that has an impact on improving individual performance. This study examines souvenir companies in Bali by taking samples of employees at the Bali Agung Company Souvenir based on non-probability sampling technique with purposive sampling method and a sample of 60 employees. Data collection was carried out using questionnaire and non-participant observation. The analysis technique in this study uses multiple linear regression analysis. The results of the analysis indicate that the Quality of Accounting Information Systems (SIA), Subjective Norms, and Ease of Use have an effect on Individual Performance. Keywords: SIA quality, subjective norms, ease of use, individual performance